2022
DOI: 10.1002/edn3.355
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA metabarcoding read numbers and their variability predict species abundance, but weakly in non‐dominant species

Abstract: Metabarcoding of environmental DNA (eDNA) provides more comprehensive, efficient, and non‐invasive sampling of biological communities than conventional methods. However, limitations of metabarcoding include taxon‐specific biases in amplification and sequencing that distort assessments of community composition. Further, hyper‐abundant species may disproportionately affect community composition assessments and impair the detection of rare species (i.e., “species masking”). In this study, we examine methodologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…A number of studies have supported this hypothesis by demonstrated that integrating allometry into metrics of organism abundance can strengthen correlations between quantitative eDNA data and population/species abundance in natural ecosystems (8,9,15,16). However, these studies have integrated allometry by applying data 'corrections' to population-level organism abundance variables, i.e., by expressing organism abundance as the sum of individual mass values within a population raised to the power of an allometric scaling coefficient ('b'), with the value of b depending on the rate at which eDNA production scales with individual body size (8,9,15,16).…”
Section: Empirical Studies Typically Show Positive Correlations Betwe...mentioning
confidence: 95%
See 1 more Smart Citation
“…A number of studies have supported this hypothesis by demonstrated that integrating allometry into metrics of organism abundance can strengthen correlations between quantitative eDNA data and population/species abundance in natural ecosystems (8,9,15,16). However, these studies have integrated allometry by applying data 'corrections' to population-level organism abundance variables, i.e., by expressing organism abundance as the sum of individual mass values within a population raised to the power of an allometric scaling coefficient ('b'), with the value of b depending on the rate at which eDNA production scales with individual body size (8,9,15,16).…”
Section: Empirical Studies Typically Show Positive Correlations Betwe...mentioning
confidence: 95%
“…The copyright holder for this preprint this version posted December 9, 2022. ; https://doi.org/10.1101/2022.12.06.519311 doi: bioRxiv preprint eDNA data and population/species abundance in natural ecosystems (8,9,15,16). However, these studies have integrated allometry by applying data 'corrections' to population-level organism abundance variables, i.e., by expressing organism abundance as the sum of individual mass values within a population raised to the power of an allometric scaling coefficient ('b'), with the value of b depending on the rate at which eDNA production scales with individual body size (8,9,15,16). While such transformations reflect the functional relationships between eDNA and organism abundance, to facilitate the inference of 'unseen' N and biomass from quantitative eDNA data such 'corrections' must be applied to the 'eDNA-side' of equations (17).…”
Section: Empirical Studies Typically Show Positive Correlations Betwe...mentioning
confidence: 99%
“…Although the authors observe that read count data were positively correlated with species abundance, they note that variance in read count among spatial replicates may exhibit a more reliable relationship with organism abundance because biases in detection/amplification of eDNA from dominant taxa can strongly affect correlations with total read numbers. Skelton et al (2023) also find that read count data was more closely related to allometrically corrected biomass data (i.e., reflecting total surface area) compared with the numerical abundance of species.…”
Section: Inferring Organism Abundance From Quantitative Edna Datamentioning
confidence: 97%
“…A number of studies in this Special Issue add to the growing consensus that temperature is a particularly important variable to consider when interpreting quantitative eDNA signals. While the previous studies focused on eDNA/abundance relationships among populations within a single species, Skelton et al (2023) and Yates et al (2023) examine relationships between quantitative metabarcoding data and interspecific abundance. Skelton et al (2023) examine relationships between metabarcoding read count and fish species abundance in a garden pond treated with the piscicide rotenone.…”
Section: Edna Dynamic S In Natur Al Ecosys Temsmentioning
confidence: 99%
See 1 more Smart Citation